Design, synthesis, and biological evaluation of novel aminobisphosphonates possessing an in vivo antitumor activity through a gammadelta-T lymphocytes-mediated activation mechanism. - Simoni, D; Gebbia, N; Invidiata, F; Eleopra, M; Marchetti, P; Rondanin, R; Baruchello, R; Provera, S; Marchioro, C; Tolomeo, M; Marinelli, L; Limongelli, V; et al. (2008)
A small series of aminobisphosphonates (N-BPs) structurally related to zoledronic acid was synthesized with the aim of improving activity toward activation of human gammadelta T cells and in turn their in vivo antitumor activity. The absence of the 1-OH moiety, together with the position and the different basicity of the nitrogen, appears crucial for antitumor activity. In comparison to zoledronic acid, compound 6a shows a greater ability to activate gammadelta T cells expression (100 times more) and a proapoptotic effect that is better than zoledronic acid. The potent activation of gammadelta T cells, in addition to evidence of the in vivo antitumor activity of 6a, suggests it may be a new potential drug candidate for cancer treatment.